125k views
0 votes
Solve the simultaneous equations
4x+3y=11
2x-y=-2

User Idej
by
4.6k points

2 Answers

6 votes

Answer:


x = (1)/(2)


y = 3

Explanation:

Multiply the bottom equation by -2.


- 2( - 2x - y = - 2) = - 4x + 2y = 4

Add the new equation to top equation.


5y = 15


y = 3

Know plug 3 in one of the equations to find x.


4x + 3(3) = 11


4x = 2


x = (1)/(2)

User Marc Intes
by
5.1k points
7 votes

Answer:

(
(1)/(2), 3 )

Explanation:

Given the 2 equations

4x + 3y = 11 → (1)

2x - y = - 2 → (2)

Multiplying (2) by 3 and adding to (1) will eliminate the y- term

6x - 3y = - 6 → (3)

Add (1) and (3) term by term to eliminate y

10x + 0 = 5

10x = 5 ( divide both sides by 10 )

x =
(1)/(2)

Substitute x =
(1)/(2) into either of the 2 equations and solve for y

Substituting into (1)

4 (
(1)/(2) ) + 3y = 11

2 + 3y = 11 ( subtract 2 from both sides )

3y = 9 ( divide both sides by 3 )

y = 3

solution is (
(1)/(2), 3 )